Los Cetpro como alternativa para fortalecer la productividad del capital humano y la transitabilidad a la educación superior de grupos en condiciones de vulnerabilidad en el Perú - Gavino Ramírez, Thalía Amelita (2024)
The Peruvian state has developed national policies that largely address the population seeking access to Technical Productive Education (TPE). However, these efforts prove insufficient in addressing the complex public issue of accessing elementary-level technical education. A significant portion of the population aiming to enter the National Center for Technical Education (CETPRO) as a prominent alternative does not necessarily find optimal conditions, leading to the perception of CETPRO as an unattractive option. Moreover, considering CETPRO as an integrated modality, the transition from elementary to higher education is not viewed as a viable opportunity to cultivate a competitive workforce in the labor market.